FREKUENSI DAN PENYEBARAN ALEL GOLONGAN DARAH A B O SISWA SMUN I SUKU BANGSA MELAYU DI KECAMATAN RUPAT KABUPATEN B ENGKALIS RIAU - Darmawati '; Evi Suryawati; Edi Suhendri (Program Studi Pendidikan Biologi, 2005)
The objective of this research was to examine the allele frequency and dissemination A BO blood group of SMUN I Melayu student, Bengkalis regency. This research have done on November 2001 – February 2002. Survey method was used in this study. The parameter observation was allele frequency IA, lB, and IO. Data analyzed by using Hardy Weinberg Law and chi square. The results shows that the allele frequency IA (0,152), lB (0,326), 1° (0,522). There was no equilibrium in allele dissemination. Kay words : ABO blood group, dissemination, equilibrium. SMUN I Bengkalis regency.